Epinephrine Augments Platelet Recruitment to Immobilized Collagen in Flowing Blood - Evidence for a von Willebrand Factor-mediated Mechanism - Mustonen, Pirjo; Lassila, Riitta (Thrombosis and Haemostasis, 1996)
Although elevated plasma epinephrine (epi) levels are associated with clinical atherothrombosis, the role of epi in platelet-vessel wall interaction has not been established. Our aim was to study the effect of high physiological epi (10 nM) in an experimental model which tests the interaction between platelets and immobilized collagen in whole blood. Shear forces and anticoagulation were modulated. Epi significantly enhanced platelet deposition, but only at high shear rate (1,600 s-1)- In PPACK- or LMWH-anticoagulated blood, the increase in platelet deposition was 32 to 85 % (p <0.02-0.05). Furthermore, platelet aggregation was cotriggered with subthreshold concentrations of epi and ristocetin, and monoclonal antibodies against glycoprotein (GP) lb (AN 51 and SZ 2) attenuated epi-induced aggregation. We conclude that epi is capable of augmenting platelet functions, which are dependent on the interaction of vWF with GP lb and GP IIb/IIIa. Via this mechanism epi may promote arterial thrombosis in vivo.